PENGARUH EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa) TERHADAP MOTILITAS SPERMATOZOA TIKUS JANTAN (Rattus norvegicus) GALUR WISTAR DENGAN PAPARAN ASAP ROKOK - Nurus Sa'adah (2020)
Cigarette smoke contains gas and particulates that have the potential to form free radicals. The content of excessive free radicals can cause oxidative stress which causes a decrease in sperm quality. Calyx roselle contains flavonoids and ascorbic acid which function as an antioxidant that can weaken the excess of free radicals. This study aims to determine the effect of calyx roselle extract on the quality of spermatozoa motility in male Wistar strain rats with exposure to cigarette smoke. 28 rats were divided into 4 groups, each group consisted of 7 rats, namely positive control given 5 cc CMC and cigarette smoke 2 sticks / day, negative control was given standard 511 food only, treatment 1 was exposed to 2 cigarette smoke sticks / day and calyx roselle extract dose 270 mg / kg/bb, and treatment 2 exposed to 2 cigarette smoke / day and calyx roselle extract dose 540 mg / kg/bb. The research was 52 days with 7 days of acclimatization. The average percentage of spermatozoa motility in the positive control group, negative control, treatment 1, and treatment 2 were 40.29%, 67.57%, 55.24%, 63.04%. After statistical analysis with the One way Anova test and Post Hoc Benferonni, the result showed p value= 0.000 (p <0.05) means that there are significant differences between positive controls and other groups. The study concluded that exposure to cigarette smoke could reduce the average percentage of spermatozoa motility and the administration of calyx roselle extracts at a dose of 270mg / kg / bb / day and 540 mg / kg / day to improve the motility of spermatozoa exposed to cigarette smoke.